Evolutionary Trends in Traditional Women’s Wedding Attire: A Case Study of Pesisir Selatan Regency - Febryanti, Dira; Yuliarma, Yuliarma (Gorga : Jurnal Seni Rupa, 2025)
The transformation of traditional women's wedding attire in Pesisir Selatan Regency is influenced by the evolution of time, technology, and fashion trends. This shift affects clothing arrangements, design, and aesthetic values. If not properly documented, there is a concern that future generations may lose their cultural identity in traditional wedding attire. Therefore, this study aims to describe the changes in clothing arrangements, design, and aesthetic values of traditional women's wedding attire in Pesisir Selatan Regency.This study employs a qualitative descriptive method and was conducted from July 30, 2023, to November 2024, using both primary and secondary data. The analysis is conducted through data reduction, data presentation, and conclusion drawing, while data validity is ensured through triangulation, peer examination, and auditing. The findings reveal significant changes: the baju kurungbasiba has transitioned into a baju kurung pas badan, the sarungsongketbalapak has been replaced with fabric matching the attire, and the tokah, originally a long shawl, has become more practical. Accessories such as sunting and jewelry have also undergone modernization.In terms of design, there have been transformations in silhouette, color, material, motifs, and decorative techniques. These changes reflect an adaptation to fashion trends but may also diminish cultural authenticity. Efforts toward preservation are necessary to ensure that cultural values remain intact.